Yo Jyo Hen Shi Ko (YHK) Modulates the Expression of Proteins Involved in de novo Lipogenesis and Lipid Exportation in Experimental Nonalcoholic Steatohepatitis (NASH) - Pereira, Isabel Veloso Alves; Souza de Oliveira, Claudia Pinto Marques; Stefano, José Tadeu; Halla, Nathalia Cavalheiro; Alves, João Avancini Ferreira; Laurindo, Francisco Rafael Martins; Carrilho, Flair José (Journal of Pharmacy and Nutrition Sciences, 2013)
Previous study by our group showed the protective effect of Yo Jyo Hen Shi Ko (YHK) a natural compound in experimental nonalcoholic steatohepatitis (NASH). The aim of this study was to evaluate whether YHK modulates lipid metabolism. NASH was induced in male ob/ob mice by methionine/choline-deficient (MCD) diet for 4 weeks. YHK-treated animals (YHK) received YHK solution orally (20 mg/kg/day) by gavage while MCD (n=6) group received only vehicle. The control animals (CTRL; n=6) received standard diet. Liver fragments were collected for mRNA and protein isolation. The analysis of gene expression and protein was performed by RT-qPCR and western blot, respectively. A significant decrease in srebp1c mRNA and protein expression and fasn mRNA expression was observed in MCD+YHK group. A significant increase in MTP protein expression was observed in the MCD+YHK vs MCD group while a decreased expression was observed in the MCD vs CTRL group. The expression of the scd1 in the MCD group was diminished. The Perilipin protein expression was augmented in the MCD group in comparison with MCD+YHK and CTRL groups. YHK modulated genes involved in the synthesis and exportation of hepatic lipids, probably limiting hepatocyte lipid accumulation, reducing lipogenesis and upregulating lipid exportation suggesting that the YHK can be a promising drug for treat non-alcoholic fatty liver disease (NAFLD).